Maternal characteristics at birth and weaning in guinea pigs of the central coast of Peru - Rodríguez L., Humberto (2015)
The study was carried out at the Cieneguilla guinea pig farm of La Molina National Agrarian University, Lima. The objective of the study were to evaluate the association of fixed factors such as season (E), parity (NP), and covariates such as maternal weight at parity (PMP), total born (TN), number of live births (LB) and age at weaning (EDC) with total born (TN), number born alive (NV), number weaned (ND), litter weight at birth (PCN), and litter weight at weaning (PCD), and to estimate phenotypic correlations between the maternal traits. Data was collected from 1302 litters collected from January 2009 to July 2010. Analysis of variance and F tests were performed using the GLM procedure of SAS (v. 9.1). The statistical analysis for TN and NV adjusted for the covariate PMP differences were obtained for E and NP (p<0.01); for ND adjusted for the covariate PMP differences were obtained for E (p<0.01); for PCN adjusted for the covariate PMP differences were found for E and NP (p<0.01); and for PCD adjusted for covariates PMP, ND and EDC differences were obtained for E, NP and E*NP (p<0.01). Estimated phenotypic correlations were all positive, moderate to high, and highly significant (p<0.01).